If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + 2) + -11 = 21 + 4 Reorder the terms: -6(2 + x) + -11 = 21 + 4 (2 * -6 + x * -6) + -11 = 21 + 4 (-12 + -6x) + -11 = 21 + 4 Reorder the terms: -12 + -11 + -6x = 21 + 4 Combine like terms: -12 + -11 = -23 -23 + -6x = 21 + 4 Combine like terms: 21 + 4 = 25 -23 + -6x = 25 Solving -23 + -6x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '23' to each side of the equation. -23 + 23 + -6x = 25 + 23 Combine like terms: -23 + 23 = 0 0 + -6x = 25 + 23 -6x = 25 + 23 Combine like terms: 25 + 23 = 48 -6x = 48 Divide each side by '-6'. x = -8 Simplifying x = -8
| -3(y+5)=15 | | 2overs-7=11 | | -9=-4(u-18)+-5 | | 6x3/6 | | 13+2p=-5-6p | | 0.09xX=110.30 | | X+(x-1)=2(x+3) | | 12x-2m= | | 3x4/9= | | -5x+2(4x-15)=-63 | | -3(-7w+4)-3w=4(w-5)-4 | | W=1000-0.2t | | 28a^3b^4+20a^2b^2-16ab^3= | | x^8=140 | | 40x-40=28 | | 67+4y-30=15y-12-4y | | 9+3y-3=7y+15-3y | | 8x+3y=67 | | 8x-5y=-9 | | 18+-9= | | V(w-l)=p | | 93-(7x+6)=7(x+6)+x | | 2x^2+14x+59=0 | | Ab+c=2 | | 0=p-20/-2 | | 8x+9y-(2x+y)= | | log(x)+8.75=0 | | -2(6x-7)+6x=5+2(2x-3) | | j+16=-10-j | | 20sinx=10 | | 10x+9-9x-15= | | 4n-40=7(-2nt+2) |